Community care for Indigenous older people: An update. (11th March 2016) - Lindeman, Melissa A; Smith, Kate; LoGiudice, Dina; Elliott, Mark
Abstract : In this brief paper, we outline some important messages in the literature pertaining to community care for Indigenous older people. Such literature has been scarce until relatively recently. These key messages are particularly important as aged care sector reforms are implemented. We highlight significant research findings concerning health, care preferences and service delivery challenges for the provision of community care for this population group. To be successful, a service needs to be relevant, and to be relevant, services need to take a community development approach in their development and ongoing management.